Problems in the Science and Mathematics of 'The Logic of Scientific Discovery' - Alan B. Whiting (Quanta)
Professor Sir Karl Popper (1902-1994) was one of the most influential philosophers of science of the twentieth century. However, in his most famous work 'The Logic of Scientific Discovery' he displays troubling misunderstandings of science and mathematics at a basic level. These call into question his conclusions concerning the philosophy of science.